Implementasi Metode Design Thinking Pada Perancangan UI/UX Design Aplikasi Dagang.in - Cahya Sonny Surachman; Muhammad Riyan Andriyanto; Catur Rahmawati; Pristi Sukmasetya (TeIKa, 2022)
The spread of Corona Virus Disease 2019 (COVID) is very disturbing for MSMEs, especially micro MSMEs. In this case, itinerant traders need convenience in trading during the pandemic because the government has imposed several policies to deal with COVID-19. The policy implemented was emergency PPKM which resulted in road access in several areas being closed. According to the Kemenkop MSMEs, it is estimated that 37,000 MSMEs will provide reports on the impact felt by the implementation of the new policy. Therefore, this application is designed by providing solutions as a form to make trading easier and increase Indonesia's economic growth. In this design using the design thinking method which consists of empathize, define, ideate, prototype, and test stages. After the development, finally got the results to create a mobile application model with the name "Dagang.in" which is equipped with chat features, location track, turnover bookkeeping, and digital wallet. At the testing stage using the maze platform to facilitate application testing. There are 5 respondents in prototype testing. The average success of the test is 85% based on predetermined metrics in the form of task 1 having 80% success, task 2 having 90% success, task 3 having 75% success, task 4 having 100% success and task 5 having 80 success %. In the testing phase the user, can complete the task but there are some tasks that have difficulty completing. It can be interpreted that in this design it is necessary to improve performance so that users do not feel confused or have difficulties when using the product.